2014
DOI: 10.1109/tasc.2013.2285235
|View full text |Cite
|
Sign up to set email alerts
|

Multipoles Induced by Inter-Strand Coupling Currents in LARP <formula formulatype="inline"> <tex Notation="TeX">$\hbox{Nb}_{3}\hbox{Sn}$</tex></formula> Quadrupoles

Abstract: The U.S. LHC Accelerator Research Program has been developing Nb 3 Sn quadrupole magnets of progressively increasing performance and complexity for the High-Luminosity LHC project. The magnets are wound with Rutherford cables following the wind-and-react process. The resulting inter-strand coupling can generate strong field distortions during current ramp. The latest series of 120 mm aperture magnets (HQ) are designed and built for high field quality, offering an opportunity for detailed studies of these effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Detailed analysis [11] led to critical revisions of the coil parameters and components which were validated through dedicated tests in a mirror structure [12][13] and gradually implemented in the HQ02 series [14]. The HQ02a model confirmed that the previous performance issues had been resolved, but its gradient was limited to 182 T/m due to the choice of a conservative pre-load level [15][16][17]. The next assembly, HQ02b, featured an increased pre-load and achieved a maximum gradient of 194 T/m at 1.9K, corresponding to 94% of the short sample limit [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed analysis [11] led to critical revisions of the coil parameters and components which were validated through dedicated tests in a mirror structure [12][13] and gradually implemented in the HQ02 series [14]. The HQ02a model confirmed that the previous performance issues had been resolved, but its gradient was limited to 182 T/m due to the choice of a conservative pre-load level [15][16][17]. The next assembly, HQ02b, featured an increased pre-load and achieved a maximum gradient of 194 T/m at 1.9K, corresponding to 94% of the short sample limit [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, some non-allowed components (a3, a4, a7 and a8) show larger ramp rate dependence. They are a factor 10 times smaller than seen in HQ01 [14] (un-cored cable), a factor 5 times smaller than in HQ02 [15] (core coverage 60 %) and a factor 2 times larger than in the CERN 11 T [16] (core coverage 90 %). When ramping stops during the stair step measurements, multipole decay of the non-allowed harmonics with a stronger dependence on the ramp rate is observed at each measurement level.…”
Section: Inter-strand Coupling Currents Effectmentioning
confidence: 71%
“…If a low electrical contact resistance is required (Section 3.4), would it lead to pronounced dynamic field errors that depend on the current ramp rates as observed in LTS magnets [181][182][183][184][185][186]? Measurements from recent Roebel and CORC R dipole magnets show no pronounced dynamic field errors [174,187].…”
Section: What Is the Field Quality Of Rebco Accelerator Magnets?mentioning
confidence: 99%